2020
DOI: 10.1002/jbm.a.36988
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized extracellular matrix‐rich hydrogel–silver nanoparticle mixture as a potential treatment for acute liver failure model

Abstract: Acute liver failure (ALF) occurs due to severe liver damage that triggers rapid loss of normal liver function. Here, we investigate the usefulness of an injectable liver extracellular matrix (LECM)-rich hydrogel generated from an optimized decellularization protocol incorporated with silver nanoparticles (AgNPs) as a promising therapy for ALF. First, we optimized a non-destructive protocol for rat liver decellularization to obtain ECM-rich well-preserved scaffold. Then, LECM hydrogel generated from two commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…ECM has been predominantly obtained through animal organ and tissue decellularization using different chemical detergents 62 . This is a critical step because the choice of detergent treatment has been shown to affect gelation kinetics, mechanical properties and biological activity of the resulting ECM hydrogels 35 , 58 , 63 . While some studies have reported the use of a single detergent treatment for successful decellularization of liver tissues 27 , 29 , 34 , other studies have shown improved efficiency of decellularization by combinational use of detergents 20 , 22 , 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ECM has been predominantly obtained through animal organ and tissue decellularization using different chemical detergents 62 . This is a critical step because the choice of detergent treatment has been shown to affect gelation kinetics, mechanical properties and biological activity of the resulting ECM hydrogels 35 , 58 , 63 . While some studies have reported the use of a single detergent treatment for successful decellularization of liver tissues 27 , 29 , 34 , other studies have shown improved efficiency of decellularization by combinational use of detergents 20 , 22 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies, however, we achieved complete solubilization at room temperature 30 , 64 . The majority of previous studies have used unfunctionalized, solubilized liver ECM to encapsulate liver cells by spontaneous gelation at 37°C 22 , 26 , 27 , 31 , 32 , 34 , 35 . While these studies have collectively demonstrated maintenance of liver-specific functions, thermal self-assembly of ECM hydrogels is a largely uncontrolled, time-consuming process which leaves little room to tune key physicochemical matrix parameters such as stiffness and porosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cell-containing hydrogels can then be injected for minimally invasive delivery into irregular spaces, [68][69][70] applied topically or used for 3D printing or electrospinning. 57,71 Some of the medical conditions for which decellularised ECM-based hydrogels have been investigated include type 1 diabetes, 70 myocardial infarction by replacing damaged cardiac tissue, 68,69 peripheral artery disease, 72 skin wound healing, 73 keratoconus by bioprinting a corneal stromal substitute, 71 acute liver failure, 74 chronic fibrotic diseases 75 and inflammatory bowel disease. 76 The impact of the decellularisation method on the ECM-derived hydrogel has been shown by several studies.…”
Section: Hydrogels With Decellularised Matricesmentioning
confidence: 99%
“…These forms are fabricated using digested ECM, homogenized ECM, or ECM ink, respectively. These ECM forms could be used for cell delivery, but they have relevant limitations, mainly due to the additional loss of biochemical components during the digestion and fabrication processes [97,[109][110][111][112][113][114][115][116].…”
Section: Bioengineered Liver Scaffolds and Their Transplantationmentioning
confidence: 99%